Experimental investigation on performance, combustion and emission analysis of a direct injection diesel engine fuelled with rapeseed oil biodiesel. (15th June 2019) - Raman, L. Anantha; Deepanraj, B.; Rajakumar, S.; Sivasubramanian, V.
Abstract: Depletion of fossil fuel resources and continuous release of greenhouse gasses to the environment forces the researchers to develop alternative fuel technologies that are environmentally more acceptable. Trans-esterified vegetable oil derivatives also called 'biodiesel' appear to be the most convenient method of utilizing bio-origin vegetable oils as replacement fuels in diesel engines. In the present study, biodiesel was prepared from non-edible rapeseed oil through the trans -esterification process and the property of biodiesel was compared with standard diesel fuel. The methyl esters of vegetable oils cope well with the existing engine hardware and do not require noticeable modification. Experiments were carried out to analyse the performance, combustion and emission characteristics of a four stroke, single cylinder 5.95 kW, direct injection diesel engine fuelled with diesel, rapeseed oil biodiesel and diesel–biodiesel blends at a constant injection pressure of 200 bar. The performance parameters such as brake thermal efficiency, brake specific energy consumption, exhaust gas temperature and combustion characteristics such as in-cylinder pressure, heat release and ignition delay of the engine were evaluated. Unburned hydrocarbon, carbon monoxide, oxides of nitrogen and smoke emission of the engine were also measured for all the test fuels. The results of the experimental investigation with biodiesel blends were compared with that of baseline diesel. The test results revealed that B25 blend can be used in the diesel without making any modification in the engine with acceptable thermal efficiency and improved exhaust emissions.